2019
DOI: 10.3389/fneur.2019.00513
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Coagulation and Fibrinolysis Predicting the Outcome of Acute Ischemic Stroke Thrombolysis Treatment: A Review of the Literature

Abstract: Intravenous administration of recombinant tissue plasminogen activator (rt-PA) has been proven to be safe and effective in the treatment of acute ischemic stroke. Little is known, however, why this treatment is less effective in some patients while in others life-threatening side-effects, e.g., symptomatic intracerebral hemorrhage might occur. Clinical failure of thrombolysis related to absent or partial recanalization or reocclusion as well as hemorrhagic complications of thrombolysis are possibly related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 83 publications
(117 reference statements)
4
45
0
1
Order By: Relevance
“…Studies showed that a decrement in 2 hours postthrombolysis fibrinogen levels to less than 2 g/L increased the odds of an early sICH by 12.82 times. 24 Our study also demonstrated that the serum fibrinogen levels fell significantly after thrombolysis, the mean fibrinogen decreasing by 7% (p < 0.0001) and we recorded an sICH rate of 13.33%. The Alteplase-Tenecteplase Trial Evaluation for Stroke Thrombolysis study also demonstrated that alteplase was associated with prolongation of prothrombin time, reduction of plasminogen and fibrinogen levels, and elevation of FDP and D-dimer levels.…”
Section: Discussion On Fibrinogen As a Biomarkersupporting
confidence: 77%
See 1 more Smart Citation
“…Studies showed that a decrement in 2 hours postthrombolysis fibrinogen levels to less than 2 g/L increased the odds of an early sICH by 12.82 times. 24 Our study also demonstrated that the serum fibrinogen levels fell significantly after thrombolysis, the mean fibrinogen decreasing by 7% (p < 0.0001) and we recorded an sICH rate of 13.33%. The Alteplase-Tenecteplase Trial Evaluation for Stroke Thrombolysis study also demonstrated that alteplase was associated with prolongation of prothrombin time, reduction of plasminogen and fibrinogen levels, and elevation of FDP and D-dimer levels.…”
Section: Discussion On Fibrinogen As a Biomarkersupporting
confidence: 77%
“…Bagoly et al's review article demonstrated that the assessment of pre-and postthrombolysis plasma fibrinogen levels was potentially useful to predict postthrombolysis sICH but more data are needed to establish its association with unfavorable outcome. 24 The study was limited by small sample size, suffers from the probability of selection bias for not including a control group consisting of patients not receiving thrombolytic treatment, our inability to estimate FDP levels in all patients, lack of a long-term follow-up, and lack of MRIbased protocols prior to thrombolysis, thereby, hindering our ability to test leukoaraiosis, microbleeds, and low ADC coefficient as predictors of sICH. Therefore, the results should be confirmed in multicenter cohort studies.…”
Section: Discussion On Fibrinogen As a Biomarkermentioning
confidence: 99%
“…The non-TIA <24-hour ischemic stroke group analyzed in this study was older (68.08 ± 14.47) than patients reported in other studies (mean age of 63) [1]. Moreover, the TIA-24hr-ischemic stroke population in this study consists of a significant proportion of patients > 80 years, not excluded from rtPA in line with AHA guidelines [24] and reported to be safe by several studies [25][26][27]. The prevalence of a prior TIA in patients with ischemic stroke in the general population is between 7% to 40% [13,28,29].…”
Section: Discussionmentioning
confidence: 57%
“…The past-TIA ischemic stroke group analyzed in this study was older (68.08 ± 14.47) than patients reported in other studies (mean age of 63) [1]. Moreover, the recent-TIA ischemic stroke population in this study consists of a significant proportion of patients > 80 years, not excluded from rtPA in line with AHA guidelines [24] and reported to be safe by several studies [25][26][27]. The prevalence of a prior TIA in patients with ischemic stroke in the general population is between 7 to 40% [13,28,29].…”
Section: Discussionmentioning
confidence: 69%